(untitled) (Update Dental College Journal, 2014)
Background: Drug utilization studies are pre requisite for the formulation of drug policies. They offer useful methods for teaching and training in drug therapy and also identify the problems that arise from drug usage in healthcare delivery system and highlight the current approaches to the rational use of medicines. Objectives: The main objective of the prescription audit or evaluation was to measures for improving the prescription practices and to generate information on the core prescribing indicators proposed by the World Health Organization (WHO). Methods: This was a descriptive type of cross sectional study. The study was conducted in the Out Patient Department (OPD) of Dermatology & Venereology in a tertiary care private hospital, Dhaka, Bangladesh in between January and March2012. A total of 300 prescriptions were obtained with the help of a pre-inserted carbon paper in a special format using WHO core prescribing indicators. Results: The average number of drugs per encounter was 3.8 and no single drug was prescribed by generic name. Use of antibiotic (56% of encounters) was frequent, but injection use (2.67% of encounters) was within the recommendation of WHO. The use of fixed drug combinations (FDCs) was 15.28% of prescribed drugs. Only 22.08% drugs were prescribed from national essential medicine list. Conclusion: The findings from the current study showed a trend towards inappropriate prescribing. DOI: http://dx.doi.org/10.3329/updcj.v4i1.21158 Update Dent. Coll. j: 2014; 4 (1): 04-09